The Impact of Customer Capital on Enhancing the Work Environment: An Analytical Study At Rafidain Bank, Anbar And Fallujah Branches - Al-Ani, Saif Hamad; Al-Lami, Amer Fadous Atheeb (Journal of Economics and Administrative Sciences, 2024)
Purpose: This research works to achieve several goals, perhaps the most prominent of which is diagnosing the extent of the bank under study’s interest in applying customer capital and the work environment within it and exploiting the relationship that brings together the variables.Theoretical Framework: Based on what the researchers (Zahedi and Lapierre) mentioned, this study addresses the lack of use of marketing intelligence tools, the lack of investment in information technology, the lack of continuous updating of data, and keeping pace with developments in the external environment.Design/Methodology/Approach: The study analyzed data in banks between the Anbar and Fallujah branches (2023-2024), using the customer capital model and through its three dimensions (marketing intelligence, customer satisfaction, and customer loyalty) and their role in enhancing the work environment and its dimensions (marketing intelligence, customer loyalty, customer satisfaction, organizational chart, regulations and instructions, incentives and rewards, and working conditions).Findings: The results highlighted the presence of an influential relationship between client capital in enhancing the work environmentResearch Implications: The results confirm that there is a weakness in the customer loyalty process, and this is due to the failure to use an appropriate and effective strategy that helps it in the process of competing with banks and making appropriate decisions to face competitive challenges.Originality/Value: This study works to identify the shortage of human resources, which leads to the difficulty of providing services to its customers according to their desires and needs. The bank should invest in technological infrastructure and modernize systems to provide advanced banking services.JEL Classification: M10, M12, M15, M19.